I know the answer to this is -23, but I do not know the correct working-out to it.So please show working-out. All help is appreciated.
If a=3, b=-2 and c=-5, then the value of 6a+3a-5bsquared-abc=
$\displaystyle a = 3$
$\displaystyle b = -2$
$\displaystyle c = -5$
$\displaystyle 6a + 3a - 5b^2 - abc$
$\displaystyle = 9a - 5b^2 - abc$
$\displaystyle = 9(3) - 5(-2)^2 - (3)(-2)(-5)$
$\displaystyle = 9(3) - 5(4) - (3)(-2)(-5)$
$\displaystyle = 27 - 20 - 30$
$\displaystyle = 7 - 30$
$\displaystyle = -23$